Retirement and Informal Care-giving: Behavioral Patterns among Older Workers - Roman Raab (Publications Office of the European Union, 2017)
This paper uses panel data from the Survey of Health, Aging and Retirement in Europe (SHARE) to study the effect of care-giving on retirement. The findings suggest that care- and support-giving contributes to the retirement decision, in particular for men. While the frequency of care activities is more influential in the male retirement decision, the most important factor for both genders turns out to be out-of-household care.
Keywords: I19; J26; J22; 330; informal care-giving; retirement; economics of aging; panel data